Contributions from lighting research to sustainability and Covid-19 pandemic - Tonello, Graciela Lucia del Carmen (2023)
Besides vision, light can impact other processes such as circadian,neuroendocrine, and neurobehavioral responses. It is called nonvisualeffects of light because they are not directly involved withimage formation, and they became an additional dimension in thetraditional objectives of architectural lighting, which should providethe proper light for visual performance, for visual comfort, for theaesthetic appreciation of the space and for energy conservation. Forinstance, in working environments, light must serve not only to meettask demands but also for comfort and health.People respond to environmental exposure through a holistic processcomposed of psychobiological correlates. To date, the most studiedlight-reactive hormone is melatonin since light can have an acutesuppressive effect on this hormone. As to psychological states,seasonal affective disorder (SAD) probably constitutes the bestexample of light’s effect on mood and behavior, and the abnormalpattern of melatonin secretion in SAD sufferers is still the mainhypothesis as to the genesis of this disorder.This conference aims to show the possible contributions from thefield of lighting research to covid-19 pandemic and to post pandemiceconomy in terms of melatonin related health and wellbeing, vitamin Dproduction in response to ultraviolet radiation on the skin, and theconcept of sustainable lighting design referred to efficient lightingtechnologies such as LEDs, as well as guidelines to minimize circadiandisruption and to improve productivity.